Life after loss: A phenomenological study of the grief experience and the meaning of loss due to pandemic in adult individuals - Temmy Andreas Habibie; Husna Nabila Yode; Alifa Fadia Ainaya; Fuad Nashori (Proyeksi, 2026)
Loss is inevitable in human life. One of the most difficult forms of loss for individuals is the death of a parent. In addition to experiencing this profound loss, they also experience depression. Approximately 10-15% of individuals who experience loss experience pathological grief reactions such as depression and prolonged grief disorder. This study aims to understand the crisis experienced by individuals, the risks arising from grief, their adaptation and efforts to cope with grief, and the meaning of loss (of a parent, partner, or other family member). This study used a qualitative research method with a phenomenological approach. The sampling technique used purposive sampling with the criteria of adult individuals aged 18 to 40 who experienced the loss of a loved one due to a deadly viral infection during the pandemic. The number of participants in this study was three. Data analysis used phenomenological analysis through the stages of bracketing, intuiting, analyzing, and describing. The results showed four main themes related to loss: risk factors, impact of the loss, overcoming the loss, and meaning. Losing their parents has a significant psychological impact, but individuals are able to achieve psychological balance and build new meaning through an adaptation process that involves self-reflection, social support, and strengthening religious beliefs.